Additive properties of saturated very long chain fatty acids in castor and jojoba oils - Ossia, C. V.; Han, H. G.; Kong, H. (KOREAN SOC MECHANICAL ENGINEERS, 2008)
Tribological and oxidation stability properties of saturated very-long-chain-fatty acids present in castor and jojoba oils have been investigated by the four ball tribosystem, pressure differential scanning calorimetry, optical micrographs and electron probe micro-analysis (EPMA). Test results of the oils additized with eicosanoic and octadecanoic acids in the oils were compared with those of zinc dialkyldithiophosphate (ZDTP). Results showed that eicosanoic and octadecanoic acids possessed better antiwear and lubricity properties compared to the popular ZDTP, though with reduced oxidation stability. EPMA and optical micrographs of worn surface morphology showed that lubricating films formed by these acids were metallic salts whose breakdown was not associated with tribochemical wear surface modification of the mating pairs.
Keywords: BOUNDARY LUBRICATION; TEMPERATURE; OXIDATION; BEHAVIOR; STEEL